A panel-data analysis of the explanatory power of factor premiums on the Johannesburg Stock Exchange (JSE). Issue 2 (3rd April 2019) - Page, Daniel; Auret, Christo
ABSTRACT: A large portion of South African asset pricing literature considers the identification of investment styles present on the Johannesburg Stock Exchange (JSE). Unfortunately, the identification of an 'investment style' does not necessarily entail that the said style is an 'explanatory factor' where 'explanatory' implies that the said factor is able independently to explain a portion of the cross-sectional variation in share returns. This study considers a number of popularised investment styles which have been documented in local and international literature, namely size, value, momentum, low beta, currency risk, low volatility and liquidity. As opposed to applying portfolio sorts based on styles and estimating factor premiums via Fama-Macbeth regressions, this study applies panel data methods on a share-by-share basis. The benefit of such an approach is the ability to test numerous styles in a multivariate parametric framework despite a limited investable universe of shares. The results of the study indicate that size, value, momentum and low-market beta are priced factors that explain the average cross-sectional variation in share returns on the JSE.